Size reduction of MIMO dielectric resonator antenna for LTE application - Jamaluddin, M. H. (Institute of Electrical and Electronics Engineers Inc., 2016)
Dielectric Resonator Antenna (DRA) is interesting antenna that can give high bandwidth, high gain, no conductor loss and others. Due to these advantages, an MIMO DRA with bandwidth enhancement has been developed for LTE bands operating at 2.6GHz. The DRA is first designed using substrate permittivity of 10 and this followed with the second design using permittivity of 30. Although, the later design is much smaller in size, both can give impedance bandwidth up to 16%.